Occupational Community-Acquired Pneumonia in a Fitter-Splicer with a Significant Smoking History: A Case Report and Expanded Review of the Literature - Anthony Suranta Surbakti; Agus Juanda (The International Journal of Medical Science and Health Research, 2025)
Introduction: Community-acquired pneumonia (CAP) is a primary driver of global morbidity and mortality, with its incidence heavily influenced by host and environmental factors. While the roles of age, comorbidities, and smoking are well-established, the contribution of occupational exposures—particularly the complex and synergistic hazards faced by industrial workers—remains a critical and often under-appreciated component of risk assessment. This report presents an in-depth analysis of a fitter-splicer, a profession with a unique combination of respiratory hazards, who developed CAP, providing a platform to explore the intricate relationship between workplace environment, lifestyle factors, and infectious disease susceptibility. Case Illustration: A 50-year-old male with a 30-pack-year smoking history presented with a one-week history of a worsening productive cough, persistent fever, right-sided pleuritic chest pain, and a significant episode of hemoptysis. Physical examination revealed focal findings over the right lower lung, including decreased tactile fremitus, diminished breath sounds, and localized rhonchi, indicative of parenchymal consolidation. Laboratory investigations showed marked neutrophilic leukocytosis and a profoundly elevated C-reactive protein level (165 mg/L). A chest radiograph confirmed dense consolidation in the right lower lobe, consistent with lobar pneumonia. Despite being stratified as low severity by both the CURB-65 and Pneumonia Severity Index (PSI) scores, he was hospitalized due to his clinical presentation and occupational context. He was managed with a dual antibiotic regimen of intravenous ceftriaxone and oral levofloxacin. The patient demonstrated a favorable clinical response and was discharged after a nine-day hospital stay. Discussion: This case serves as a paradigm for the critical interplay between a patient's multifaceted occupational exposures and his extensive smoking history. The role of a "fitter-splicer" is deconstructed to reveal a dual-threat exposure profile: inhalation of metal fumes and inorganic dusts (e.g., silica) from fitting, grinding, and welding, combined with exposure to chemical vapors and organic dusts from conveyor belt splicing and vulcanization processes. These exposures are known to synergistically impair pulmonary immune defenses. This chronic occupational insult, compounded by decades of smoking-induced lung damage, created a state of profound susceptibility to infection. This decision represents a significant deviation from current evidence-based guidelines, which now strongly recommend against their routine use in non-severe CAP, reserving them for patients with severe disease characterized by a hyperinflammatory state. The differential diagnoses of tuberculosis and underlying malignancy are explored in detail, emphasizing the necessity of post-discharge radiological follow-up in this high-risk patient. Conclusion: This case underscores the clinical imperative to obtain a detailed occupational and environmental history in all patients presenting with CAP. It vividly demonstrates how combined industrial exposures and smoking can dramatically amplify pneumonia risk by overwhelming the lung's clearance and immune mechanisms. Furthermore, it highlights the urgent need for robust preventive strategies in high-risk occupations, including the stringent implementation of the hierarchy of controls in the workplace, targeted and accessible smoking cessation programs, and the proactive, guideline-driven administration of pneumococcal vaccination to this vulnerable population.